Functional Lactic Acid Bacteria in Fermented Foods: Bioactive Compounds, Health Benefits, and Food Applications - Nurchalisah Rustan Massinai (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Lactic acid bacteria (LAB) are among the most important microorganisms involved in food fermentation because of their capacity to improve food safety, physicochemical properties, sensory quality, and nutritional value. Increasing evidence has demonstrated that selected LAB strains possess functional properties that extend beyond their technological roles through the production of diverse bioactive compounds and their interactions with the host. This review provides a comprehensive overview of the biological characteristics of functional LAB, their occurrence in fermented foods, and the biosynthesis of key metabolites, including organic acids, bacteriocins, exopolysaccharides, bioactive peptides, γ-aminobutyric acid (GABA), and vitamins. Current evidence regarding the mechanisms by which functional LAB contribute to gut microbiota modulation, intestinal barrier integrity, immune regulation, antioxidant defense, and metabolic health is also discussed. The review further examines the application of functional LAB in dairy, plant-based, meat, seafood, and traditional fermented foods, together with recent advances in precision fermentation, multi-omics technologies, and microbial biotechnology that facilitate the development of next-generation functional foods. Current research challenges and emerging perspectives are also highlighted to support the scientific advancement and industrial application of functional LAB in sustainable food systems.